Show Me the Money : Access to Finance for Small Borrowers in Canada - Klyuev, Vladimir (IMF Working Papers; Working Paper ;, 2008)
This paper examines access to business finance by Canadian small and medium-sized enterprises (SMEs) and to housing finance by Canadian households (particularly non-prime borrowers) against the background of a fairly concentrated and protected banking industry. It finds access broadly adequate for the former group. However, given the dominance of the large banks and their fairly low risk tolerance, financing of riskier projects is a challenge. Problems with venture capital, plausibly related to the prevalence of tax-advantaged labor-sponsored funds, exacerbate the situation for the most innovative SMEs. The paper also finds the market for housing finance to be highly advanced and sophisticated. However, non-prime mortgage financing is in its infancy in Canada, and further development of that sector (while avoiding the excesses that beset the U.S. market in the last few years) would be beneficial. More broadly, despite recent innovations, options available to Canadians for financing house purchases are still somewhat limited, with scarce availability of mortgage maturities beyond five years particularly surprising. Further advances in securitization could help progress in both of these areas.